Resolving the orthographic ambiguity during visual word recognition in Arabic: an event-related potential investigation - Taha, Haitham; KHATEB, Asaid (Frontiers in Human Neuroscience, 2013)
The Arabic alphabetical orthographic system has various unique features that include the existence of emphatic phonemic letters. These represent several pairs of letters that share a phonological similarity and use the same parts of the articulation system. The phonological and articulatory similarities between these letters lead to spelling errors where the subject tends to produce a pseudohomophone (PHw) instead of the correct word. Here, we investigated whether or not the unique orthographic features of the written Arabic words modulate early orthographic processes. For this purpose, we analyzed event-related potentials (ERPs) collected from adult skilled readers during an orthographic decision task on real words and their corresponding PHw. The subjects’ reaction times were faster in words than in PHw. ERPs analysis revealed significant response differences between words and the PHw starting during the N170 and extending to the P2 component, with no difference during processing steps devoted to phonological and lexico-semantic processing. Amplitude and latency differences were found also during the P6 component which peaked earlier for words and where source localization indicated the involvement of the classical left language areas. Our findings replicate some of the previous findings on PHw processing and extend them to involve early orthographical processes.